Pharmaceutical Industry Independence Strategy in Supporting Defense Economic Post-Covid-19 - Isnaeniah, Risma Wati; Prakoso, Lukman Yudho; Saputro, Guntur Eko (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2023)
This article talks about health is one type of non-military threat that can disrupt the stability of a country. This is evidenced by the Covid-19 pandemic which has had a domino effect on the economic, social, and political fields of all countries in the world, including Indonesia. This article found handling Covid-19 on the health side is the availability of health workers, medical devices, and medicines. One of the obstacles faced is the limited stock of drugs due to the stagnant supply of medicinal raw materials from abroad, while 90-95% of the medicinal raw materials used by the pharmaceutical industry are still imported. With this experience, the independence of the pharmaceutical industry must be achieved without depending on foreign countries and achieving domestic resilience. In achieving this, various obstacles and barriers must be faced by the government by setting the right strategies and policies. In addition, a collaboration between the government and the pharmaceutical industry is needed so that the implementation of realizing the independence of the pharmaceutical industry is achieved effectively and efficiently.